Pedagogia social na Colômbia: possibilidades de intervenção socioeducativa no pós-conflito - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The following research proposal addresses the Social Pedagogy meeting in Colombia, through the qualitative study of the Post-conflict. The post-conflict is interpreted in this study as the period after the historic signing of the peace process between the FARC guerrillas and the national government, September 26, 2016 (official signing of the agreement). In this context is the present documentary research, from the content analysis the areas of Social Pedagogy are delimited, analyzed and interpreted as possibilities of educational intervention from the socioeconomic, sociopolitical, socio-legal and socio-cultural components. The areas are determined based on their theoretical and practical possibilities, which we reach through three routes; historical (chapter I), practical (chapter II) and analytical (chapter III).
Keywords: Pedagogia Social; Pedagogia Social; Intervenção Socioeducativa e pós-conflito; Social Pedagogy; Social Education; Socio-educational Intervention and post-conflict; CNPQ::CIENCIAS HUMANAS::EDUCACAO